JUOZAS NAUJALIS’ LITHUANIAN CHURCH PSALM BOOK (1906) IN THE CONTEXT OF PUBLISHING LITHUANIAN CHORAL MUSIC - GUDELIS, REGIMANTAS (Knygotyra, 2015)
The printing of Lithuanian songs and psalms began in Lithuania in the 19 th century already, at the time of the press ban introduced by the tsar government. Illegal Lithuanian newspapers “Aušra” (The daybreak, 1883–1889), “Tėvynės sargas” (The guard of the Fatherland), “Žinyčia”, “Varpas” (The bell), published in Tilsit, printed the first melodies of Lithuanian songs and psalms. In Tilsit in 1889 Lithuanian mass by J. Kalvaitis was published as well as multi-voices psalm book – for the catholic churches. For Lithuanian protestant churches “Giesmių balsai” (Psalm voices) by W. Hofheinz was published in 1894. In 1895 the first collection of Lithuanian folk songs for the choir Kanklės by V. Kudirka was published. Until World War I 18 collections of Lithuanian psalms and songs were published all in all. In them, including the periodicals, up to 500 songs and psalms with the Lithuanian text were published. Besides, composer Č. Sasnauskas published his own Lithuanian choral music, Requiem and other sacral works with the Latin and Russian text in St. Peterburgh. On 13th September 1865 when the tzar government introduced the ban on the national press in Lithuanian, all the Lithuanian alphabet printing houses were closed down, printing presses were destroyed. Lithuanian illegal press, including the notes was published in East Prussia in Tilsit. Here 11 Lithuanian works with notes were published until World War I, as well as 4 in Kaunas, 3 in Seinai, the rest in Heidelberg, Warsaw, Helsinki. The notation culture of the publication is different, because the quality of the notes’ publishing depended on the clients’ budget and possibilities to choose the way of printing. In Kaunas in 1906 Lithuanian church psalm book by J. Naujalis was published. It was in general the first Lithuanian catholic psalm book with notes for the choir and the organ. The Psalm book generalized the reform of the church music introduced at the beginning of the 20th century. As since the ancient times there music had been a lot of psalms of Polish origin sing in Lithuanian part of them was harmonized by J. Naujalis and included into his Psalm book. In this way the Psalm book reflected the convergence of Lithuanian–Polish singing tradition conditioned historically. J. Naujalis the Psalm book printed in M. Sokolovski and A. Estrin publishing house apparently became not only the beginning of the Lithuanian notes publishing in Lithuania, but also the sample of high quality notation culture. It is shown by the comparative analysis of the Lithuanian psalm booksong. The Psalm book was not published for the second time, because its psalms which literary text constantly improved appeared in other psalm book.